Increased Needle Nitrogen Contents Did Not Improve Shoot Photosynthetic Performance of Mature Nitrogen-Poor Scots Pine Trees - Tarvainen, Lasse; Lutz, Martina; Räntfors, Mats; Näsholm, Torgny; Wallin, Göran (Frontiers in Plant Science, 2016)
Numerous studies have shown that temperate and boreal forests are limited by nitrogen (N) availability. However, few studies have provided a detailed account of how carbon (C) acquisition of such forests reacts to increasing N supply. We combined measurements of needle-scale biochemical photosynthetic capacities and continuous observations of shoot-scale photosynthetic performance from several canopy positions with simple mechanistic modelling to evaluate the photosynthetic responses of mature N-poor boreal Pinus sylvestris to N fertilization. The measurements were carried out in August 2013 on 90-year-old pine trees growing at Rosinedalsheden research site in northern Sweden. In spite of a nearly doubling of needle N content in response to the fertilization, no effect on the long-term shoot-scale C uptake was recorded. This lack of N-effect was due to strong light limitation of photosynthesis in all investigated canopy positions. The effect of greater N availability on needle photosynthetic capacities was also constrained by development of foliar P deficiency following N addition. Thus, P deficiency and accumulation of N in arginine appeared to contribute towards lower shoot-scale nitrogen-use efficiency in the fertilized trees, thereby additionally constraining tree-scale responses to increasing N availability. On the whole our study suggests that the C uptake response of the studied N-poor boreal P. sylvestris stand to enhanced N availability is constrained by the efficiency with which the additional N is utilized. This efficiency, in turn, depends on the ability of the trees to use the greater N availability for additional light capture. For stands that have not reached canopy closure, increase in leaf area following N fertilization would be the most effective way for improving light capture and C uptake while for mature stands an increased leaf area may have a rather limited effect on light capture owing to increased self-shading. This raises the question if N limitation in boreal forests acts primarily by constraining growth of young stands while the commonly recorded increase in stem growth of mature stands following N addition is primarily the result of altered allocation and only to a limited extent the result of increased stand C-capture.